Metabolic Surgery on Patients With Polycystic Ovary Syndrome: A Systematic Review and Meta-Analysis - Yue, Wenwen; Huang, Xin; Zhang, Wenjing; Li, Shumin; Liu, Xu; Zhao, Yian; Shu, Jiaxin; Liu, Teng; Li, Weihua; Liu, Shaozhuang (Frontiers in Endocrinology, 2022)
Polycystic ovary syndrome (PCOS) is a complicated reproductive endocrine disease that is closely related to obesity. Metabolic surgery ameliorates a series of clinical manifestations and related comorbidities of PCOS. However, the overall efficacy of metabolic surgery on PCOS remains uncertain. This systematic review and meta-analysis aimed to evaluate the therapeutic effects of metabolic surgery on obese patients with PCOS. A systematic literature search for relevant studies was conducted on PubMed, Embase, Web of Science, and the Cochrane Library from inception to June 2021. Data extraction and quality evaluation were performed by three researchers, and RevMan 5.4 software was used to conduct the meta-analysis. A total of 14 studies involving 501 obese patients with PCOS were included. Incidence of PCOS in obese women ranged from 5.5% to 63.5% among the included studies. The results showed the incidence of abnormal menstruation decreased from 82% to 15% (OR=0.03, 95% confidence interval (CI): 0.01-0.08), while the incidence of hirsutism dropped from 71% to 38% (OR=0.21, 95% CI: 0.06-0.74). Serum total testosterone and free testosterone levels decreased by 25.92 ng/dL (MD = -25.92, 95% CI: -28.90--22.93) and 2.28 ng/dL (SMD = -2.28, 95% CI: -3.67--0.89), respectively. Sex hormone-binding globulin (SHBG) levels increased by 26.46 nmol/L (MD = 26.46, 95% CI: 12.97-39.95). Serum anti-Mullerian hormone (AMH) levels decreased by 1.29 ng/mL (MD = -1.29, 95% CI: -1.92--0.66). Small sample size studies revealed that pregnancy rates ranged from 95.2% to 100% postoperatively. Metabolic surgery contributed to marked improvement of abnormal menstruation, hirsutism, and levels of free testosterone, total testosterone, SHBG, and AMH in patients with PCOS. Our findings indicate that patients with PCOS are expected to benefit from metabolic surgery, and could help potentially improve their reproductive outcomes. Metabolic surgery could thus be a new viable option for the clinical treatment of PCOS.